REMOVABLE PROSTHETIC TREATMENT IN CHILDREN - literature review - Mariana Dimova-Gabrovska; Desislava Dimitrova; Vladislav A. Mitronin (Peytchinski Publishing, 2018)
The defects of the dental arches, which are the result of various genetic diseases, traumas, multiple and early childhood caries can significantly impair speech, chewing function, aesthetics and normal development of orofacial structures. In such cases, different types of removable prosthetic treatments allow recovering the three medico-biological indicators and support the correct physical and mental development of the child. The purpose of this study is to present the current scientific data on the use of the removable prosthetic treatment in children. The survey is conducted from December 2017 to February 2018. A total of 330 literary sources found by keywords are subjected to critical analysis. The results show that in children aged 3 to 14, which suffer from total or partial edentulism, prosthetic treatments are conducted with total dentures, partial dentures with bent or plastic hooks or with tooth supported overdentures. Plastic primary or permanent teeth are used following the routine clinical stages, and the constructions are continuously modified according to age-related physiological and anatomical requirements. Conclusion: Removable prosthetic treatments in children provide an opportunity for full masticatory and speech function and improves the quality of life of the kids.